Epidemiological Survey of Toxoplasma gondii and Associated Risk Factors in Ruminant Species of the Khyber Pakhtunkhwa Province of Pakistan. (3rd February 2021) - Ali, Abid; Omer, Talha; Ullah, Asad; Haleem, Abdul; Naseem, Maryam; Ullah, Mujeeb; Seemab,; Shamim, Fahad; Tehreem, Amna; Bilal, Muhammad; Khan, Muhammad Numan
Abstract : Toxoplasma infection is one of the most common human parasitic diseases. During 2018-2020, in the rural areas of three districts of Pakistan, we surveyed a total of 451 animals, belonging to different asymptomatic ruminant species, to determine the prevalence of Toxoplasma gondii antibodies. We used ELISA assay as well as recorded some associated risk factors contributing to its transmission. IgM antibodies were detected in 17% and IgG in 13.4% of ruminant samples with the highest percentage, 10% for IgM and 8.6% for IgG in sheep. A strong significant association was found between antibodies and different species (IgM, χ 2 = 29 .280, P = .000, and IgG, χ 2 = 22.580, P = .000 ), respectively. Infection with T. gondii seems mainly associated with different geographic features and the presence of cats in the environment, low hygiene water systems and livestock that are mostly dependent on outdoor drinking and grazing. There was no significant association between IgM and age grouping (χ 2 = 6.660, P = 0.840 nor for IgG (χ 2 = 8.136, P = 0.43 ). The results of this study may be considered the starting point to promote the awareness about parasitic infections in ruminants in Pakistan in order to prevent this infection from further spreading.